The Influence of Perceived Value on Destination Image (Survey at Bair Island Tourist Destination) - Fentje Salhuteru; Dady Mairuhu; Sammy Saptenno; Naddynda PN; Dian Utami Sutiksno (AIBPM Publisher, 2021)
Maritime tourism is a leading sector. However, tourist visits fluctuate. Variables that are suspected to be the cause of the fluctuating number of visits are because they have not been able to create perceived value, and the destination image is not optimal. The purpose of this study is to determine the effect of perceived value on destination image in the tourist destination of Bair Island. The type of research used is descriptive and verification. The survey was conducted using a questionnaire to 223 respondents (tourists) who are currently and have traveled to Bair Island. With a SEM (structural equation model) analysis tool using the lisrel program. The results of the descriptive research show that the destination image that they have is only good. While the results of the verification research show that the variables studied have a significant effect.